Utilização das ferramentas iLogic e iPart do autodesk inventor na confecção de conjuntos mecânicos - Mello, Victor Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work demonstrates in a didactic way the use of some specific software 3D modeling tools from Autodesk Inventor 2018. IPart and iLogic were used to perform customization and changes in the case study project, showing how these resources can streamline and facilitate changes and improvements in mechanical designs, also applying simulation resources, in this case, stress analysis in order to seek improvements and structural analysis. In this way, the Conveyor Lift was modeled using these tools to change dimensions, material and equipment parts, thus being able to generate various models quickly that were then submitted to a stress analysis process through the simulation feature to obtain improvements

Neste trabalho é demonstrada de forma didática a utilização de algumas ferramentas especificas do software de modelagem 3D, Autodesk Inventor 2018. Utilizou-se o iPart e o iLogic para realização de customização e alterações no projeto de estudo de caso mostrando como estes recursos podem agilizar e facilitar mudanças e melhorias em projetos mecânicos, aplicando também recursos de simulação, no caso, análise de tensão visando buscar melhorias e análises estruturais. Deste modo, o Elevador Transportador foi modelado, utilizando-se estas ferramentas para se alterar dimensões, material e peças do equipamento, podendo assim gerar variados modelos rapidamente que foram então submetidos a processo de análise de tensão por meio do recurso de simulação para obtenção de melhorias
Using the iLogic and iPart tools of the autodesk inventor in the making of mechanical assemblies
Keywords: Simulação (Computadores); Software; Elevadores; Computer software